Metabolite-biomarker investigations in the life cycle of and infection with Schistosoma - Legido-Quigley, C. (Parasitology, 2010)
Schistosome infection is endemic in many Third World countries and affects an estimated 200 million individuals. Over the last few years, a number of investigations have focused on small molecule biomarkers of this infection. These studies were aimed at discovering key molecules relating to the life cycle of the parasite or deciphering metabolic change in the host during infection. In this review these studies are further divided into targeted approaches to find compounds and fingerprinting techniques i.e. metabonomics. A species-specific metabolite or group of biomarkers of the infection have yet to be discovered. For this reason a critical discussion contrasting with established diagnostic methods and future prospects are also provided.